ИССЛЕДОВАНИЯ ВУЛКАНОВ КАМЧАТКИ ДИСТАНЦИОННЫМИ МЕТОДАМИ В 2005 ГОДУ - Сенюков С.Л.; Дрознина С.Я.; Нуждина И.Н.; Гарбузова В.Т.; Кожевникова Т.Ю. (My University, 2006)
MONITORING OF ACTIVE KAMCHATKAN VOLCANOESUSING REMOTE METHODS IN 2005Sergey L. Senyukov, Svetlana Y. Droznina, Irina N. Nuzhdina,Valentina T. Garbuzova, and Tatiana Y. KozhevnikovaKamchatkan Branch of the Geophysical Survey of the RAS, Petropavlovsk-Kamchatsky, 683006, RUSSIAe-mail: ssl@emsd.ruKamchatkan Branch of the Geophysical Survey (KBGS) RAS has being monitoredvolcanic activity since February 2000 (http://emsd.iks.ru/~ssl/monitoring/main.htm)using three remote methods: 1) Seismic monitoring is a leading method (processing andinterpretation of the data from automatic telemetric seismic stations); 2) Visual and videoobservation; 3) Satellite observation. Processing and interpretation of the sensor AVHRRdata from satellite NOAA. Data from KCCM (Kamchatsky Centre of Communicationand Monitoring).In 2005, Sheveluch, Kluchevskoy, Bezymianny and Karymsky volcanoes had theeruptions. Successful short-term eruption predictions (time and size) for Bezymianny andKlyuchevskoy volcanoes were made by Research Laboratory of Seismic and VolcanicActivity (KBGS) and passed to Kamchatkan Branch of Russian Advisory Council.
Keywords: Авачинский; Карымский; Корякский; Безымянный; Мутновский; Шивелуч; Ключевской; 550.34+551.21